The personal and professional qualifications and supervisory activities of private secondary school principals of Eastern Samar - Bantique, Agustina Yap 1932- ([Quezon City s.n.], 1972)
The personal and professional qualifications and supervisory activities of private secondary school principals of Eastern Samar with view to suggest guidelines for their improvement were determined
Thesis (M. Ed.)--University of the Philippines.
Keywords: School superintendents and principals -- Eastern Samar